Tackling Wicked Government Problems: A Practical Guide for Developing Enterprise Leaders - JACKSON NICKERSON, RONALD SANDERS (Brookings Institution Press, 2014)
The federal government has a leadership crisis. The problem does not originate from its career executives or those that aspire to be. Without exception or doubt, career executives are unequivocally committed to their country and to the ideals of its public ser - vice, as well as to the missions of the agencies they serve. Nor does the problem come strictly from agencies, which, to varying degrees, have invested in developing their own leaders, readying them for the difficult agency challenges they face. No, the leadership crisis derives from an institutional failure. As an institution, the federal government has no systematic, â€œwholeof- governmentâ€ approach for developing its career executives. The original vision of the Senior Executive Service cast career executives as a government-wide, enterprise leadership corps with the understanding and ability to tackle wicked challenges that span multiple government agencies. However, in the years since the 1979 inception of the Senior Executive Service, executive development has remained decidedly agency-centric, and it remains so even in the face of a growing flood of complex and unstructured enterprise- wideâ€” that is, interagencyâ€” challenges. Without a cadre of enterprise leaders, tackling the growing number of wicked government problems is likely to be hit or miss at best. This growing crisis in enterprise leadership and what to do about it is the focus of this book.